2010
DOI: 10.1165/rcmb.2009-0121oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Serotonergic System in Reduced Pulmonary Function after Exposure to Methamphetamine

Abstract: Although use of methamphetamine (MA) by smoking is the fastest growing method of administration, very limited data are available describing the effects of smoked MA. Using a murine inhalation exposure system, we explored the pulmonary effects of low-dose acute inhalation exposure to MA vapor (smoke). Inhalation of MA vapor resulted in transiently reduced pulmonary function, as measured by transpulmonary resistance, dynamic compliance, and whole-body plethysmography compared with unexposed control animals. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…In a previous study (6), it was identified that MA induced the increasedconcentration of 5-HT, which indicated that the serotonin mechanism is involved in MA-induced pulmonary toxicity. MA, as a substrate for SERT, was transported into cells and subsequently inhibited the metabolism of 5-HT by inhibiting monoamine oxidase A (6,27). The activation of SERT can promote 5-HT-impaired efferocytosis (11).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study (6), it was identified that MA induced the increasedconcentration of 5-HT, which indicated that the serotonin mechanism is involved in MA-induced pulmonary toxicity. MA, as a substrate for SERT, was transported into cells and subsequently inhibited the metabolism of 5-HT by inhibiting monoamine oxidase A (6,27). The activation of SERT can promote 5-HT-impaired efferocytosis (11).…”
Section: Discussionmentioning
confidence: 99%
“…It had been found that MA has multiple effects on the serotonergic signalling and 5-HT is capable of contributing to the development of PAH [8]. However, the effect of MA on the pulmonary vessels has not been directly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…routes where very high levels of drug would be expected to interact with the serotonergic system in the lung [1]. Depending on the degree of retention by the lung, intrinsic toxicity and individual susceptibility, pulmonary hypertension might develop as a toxic response to MA [8,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transpulmonary resistance was assessed as previously described (Wells et al 2010). Mice were challenged with vehicle (PBS), followed by increasing concentrations of methacholine (1.5, 3, 6, 12 and 24 mg/ml).…”
Section: Methodsmentioning
confidence: 99%